Towards zero bleeding after laparoscopic sleeve gastrectomy: investigating the impact of prophylactic tranexamic acid - Almalki, Owaid M. (International Surgery Journal, 2024)
Background: Laparoscopic sleeve gastrectomy (LSG) is a prevalent bariatric procedure known for its efficacy in weight loss and amelioration of obesity-related comorbidities. However, postoperative bleeding from the staple line remains a significant complication, necessitating strategies for effective hemostasis. Tranexamic acid (TXA) has shown promise in reducing bleeding complications in various surgical contexts, yet its role in LSG remains underexplored due to concerns about thromboembolic risks. Methods: This retrospective comparative analysis examines the impact of prophylactic TXA administration on perioperative bleeding in LSG patients. Two cohorts of 100 patients each, undergoing LSG before and after TXA implementation, were analyzed. Demographic, clinical, and outcome data were collected and statistically analyzed. Results: In our study, 100 patients received TXA with a mean age of 36.8±12.18 years, while another 100 formed the non-TXA group with a mean age of 37.2±11.81 years. Pre-surgery, clinical characteristics and hemodynamic parameters did not significantly differ between groups. However, post-surgery, TXA patients showed significantly elevated hemoglobin levels (p=0.019), increased hematocrit (p<0.001), higher prothrombin activity (p=0.002), decreased INR values (p=0.012), and higher fibrinogen levels (p=0.014) compared to non-TXA patients. Three non-TXA patients experienced post-operative bleeding requiring ICU admission and transfusions. The mean length of stay was 2.1±0.5 days for TXA patients and 2.2±0.03 days for non-TXA patients. No venous thromboembolism (VTE) or deaths occurred in either group. Conclusions: The integration of prophylactic TXA into perioperative protocols for LSG holds promise in optimizing hemostasis and enhancing patient outcomes. TXA serves as a valuable adjunctive strategy towards minimizing bleeding events and bolstering safety in LSG procedures.